Soil Microbial Communities Affect the Growth and Secondary Metabolite Accumulation in Bletilla striata (Thunb.) Rchb. f. - Xiao, Chenghong; Xu, Chunyun; Zhang, Jinqiang; Jiang, Weike; Zhang, Xinqing; Yang, Changgui; Xu, Jiao; Zhang, Yongping; Zhou, Tao (Frontiers in Microbiology, 2022)
Objective: Soil type can affect the growth of Bletilla striata and the accumulation of secondary metabolites in its tubers, but the biological mechanisms underlying these effects remain unclear. Methods: Based on field, we compared agronomic traits and the accumulation of secondary metabolites (extractum, polysaccharide, total phenol, militarine) in B. striata grown in sandy loam or sandy clay. In addition, we compared physicochemical properties and microbial communities between the two soil types. In pot experiments, we tested how irradiating soil or transplanting microbiota from clay or loam into soil affected B. striata growth and accumulation of secondary metabolites. Results: Sandy loam and sandy clay soils differed significantly in their physicochemical properties as well as in the structure and composition of their microbial communities. The accumulation of secondary metabolites such as militarine in B. striata was significantly higher in sandy clay than in sandy loam soil. Conversely, B. striata grew better in sandy loam soil. Pot experiment results further confirmed that the accumulation of secondary metabolites such as militarine was higher in soil transplanted with loam microbiota than in soil transplanted with clay microbiota. Conclusion: The microbiome associated with sandy clay soil can promote the accumulation of militarine in B. striata tubers, but it inhibits the growth of B. striata. In contrast, the microbiome associated with sandy loam soil can promote the growth of B. striata, but it reduces the accumulation of militarine in B. striata tubers. These results may help guide efforts to improve B. striata yield and its accumulation of specific secondary metabolites.